Maternal narcotic abuse and the newborn. Issue 1 (January 1988) - Alroomi, L G; Davidson, J; Evans, T J; Galea, P; Howat, R
Abstract : In 50 infants born to women who continued to take heroin during all or part of their pregnancy the drug withdrawal symptoms were mild and were noted in 21 infants (42%). Only nine infants required treatment. Sudden infant death syndrome occurred in two infants at 4 and 6 months.